Three essays on the state of economic science - Koopmans, Tjalling C. (New York : McGraw-Hill, 1957)
The essays reflect the particular preoccupations and limitations of their author at least as much as they reflect the current state of economic science. These preoccupations concern broadly the parallel and connected development of economic theory and economic observation and measurement in order to increase man's understanding and society's control of economic conditions. advancement. and well-being. More in particular, they concern the development and use of mathematical and statistical concepts and tools for these purposes.
Includes bibliographical references
rpm 10/07/2017
Loans
Keywords: Economics